2003
DOI: 10.1177/004051750307300611
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Stretchable Textiles with Spatial Loading

Abstract: A comparative analysis of two kinds of highly stretchable orthotropic textile materials (woven and knitted) reveals their behavior with spatial biaxial (membrane and punch) deformation. The investigation is illustrated by uncommon experimental cases when perpendicularly loaded disc-shaped specimens experience a stressed state very close to uniaxial tension, i.e., one of the two stresses of biaxial tension becomes negligibly small compared to the other. The conditions for a spatial textile shell to achieve an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Meantime the values of uniaxial extension of synthetic leather L2 were higher compared to the values of synthetic leather L1 (Table 1) in course direction by 43.02 % and in wale direction -by 459.86 %, respectively. This example proves earlier obtained findings [2] that highly stretchable and anisotropic materials (synthetic leather L2 in analysed case) in biaxial loading may experience the state close to the uniaxial tension. Hence the main loading in the presented testing falls upon less deformable course direction of synthetic leather L2 making its hanging height H 50 values more close to uniaxial extension values in course direction compared to wale direction which reached even 459.86 %.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Meantime the values of uniaxial extension of synthetic leather L2 were higher compared to the values of synthetic leather L1 (Table 1) in course direction by 43.02 % and in wale direction -by 459.86 %, respectively. This example proves earlier obtained findings [2] that highly stretchable and anisotropic materials (synthetic leather L2 in analysed case) in biaxial loading may experience the state close to the uniaxial tension. Hence the main loading in the presented testing falls upon less deformable course direction of synthetic leather L2 making its hanging height H 50 values more close to uniaxial extension values in course direction compared to wale direction which reached even 459.86 %.…”
Section: Resultssupporting
confidence: 90%
“…Up to date the problems of fitting woven and knitted fabrics to three-dimensional surfaces were analysed from the standpoint of their mechanical and physical properties [1]. The investigations were performed aiming to find out the relationships between the parameters of uniaxial and biaxial behaviour [2] and seeking to define the effect of materials anisotropy level upon the shapes of spatial objects obtained under biaxial loadings [3]. Other investigations showed that pre-tension is an effective method to improve the quality of the shaped composite parts [4].…”
Section: Introduction *mentioning
confidence: 99%
“…2 In clothing applications, bagging deformation is a good example of these shells. 3 In medical applications, these shells are usually named pressure garments and are widely used around the world. For some issues (e.g., varicose veins, hypertrophic scars), exerting pressure on the limb is an efficient method of treatment; this is known as pressure therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The wellknown and widely used method for the investigation of textiles and polymer materials is called punch deformation. 3 In the punch deformation method, the sheet is loaded by a rigid spherical punch; therefore, an internal tensile stress is induced in the sheet, and also, interfacial pressure is created between the punch and the sheet. Amirbayat 15 studied punch deformation using Laplace law.…”
Section: Introductionmentioning
confidence: 99%
“…The first method is sufficiently well‐studied in aspect of theory and is widely used for the investigation of mechanical properties of materials 1–8. In this case, a disc‐shaped specimen restricted in the clamp is loaded by a punch until puncture (breaking) of specimen or until unchangeable value of punch force or punch deformation, i.e., P = const or H = const.…”
Section: Introductionmentioning
confidence: 99%